2017
DOI: 10.1038/icb.2017.38
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T cells contribute to lacrimal gland pathology in the nonobese diabetic mouse model of Sjögren syndrome

Abstract: Sjögren syndrome is an autoimmune disease characterized by targeted destruction of the lacrimal and salivary glands resulting in symptoms of severe ocular and oral dryness. Despite its prevalence, the mechanisms driving autoimmune manifestations are unclear. In patients and in the nonobese diabetic (NOD) mouse model of Sjögren syndrome, lymphocytic infiltrates consist of CD4 and CD8 T cells, although the role of CD8 T cells in disease pathogenesis has been largely unexplored. Here, we evaluated the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 70 publications
2
54
0
1
Order By: Relevance
“…CD8+ T cells localize around the apoptotic acinar epithelial cells in patients with SS (). Another recent study found that CD8+ T cells can promote dacryoadenitis and mediate epithelial cell damage in NOD mice . In this study, we found that CD8+ T cells were dominant both in the labial salivary glands of patients with SS and in the salivary glands of p40 −/− CD25 −/− mice.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…CD8+ T cells localize around the apoptotic acinar epithelial cells in patients with SS (). Another recent study found that CD8+ T cells can promote dacryoadenitis and mediate epithelial cell damage in NOD mice . In this study, we found that CD8+ T cells were dominant both in the labial salivary glands of patients with SS and in the salivary glands of p40 −/− CD25 −/− mice.…”
Section: Discussionsupporting
confidence: 59%
“…Genome‐wide association scans and meta‐analyses of SS have revealed a strong association of the disease with several HLA molecules , implicating T cells as a major driver of SS. Although previous studies have found that CD4+ T cells constitute the majority of infiltrating cells, recent findings have suggested that CD8+ T cells are just as abundant as CD4+ T cells and may play an equally critical role in SS . However, the CD8+ T cell subpopulations implicated in the pathologic development and progression of SS have not yet been identified.…”
Section: Introductionmentioning
confidence: 94%
“…Male and female NOD/ShiLtJ (NOD), castrated and sham‐castrated male NOD, and NOD.CB17‐ Prkdc scid / J (non‐obese diabetic– severe combined immunodeficient; NOD‐SCID) mice were purchased from The Jackson Laboratory (Bar Harbor, ME). NOD mice expressing the bicistronic Foxp3‐green fluorescent protein (Foxp3 GFP ) reporter construct knocked into the endogenous Foxp3 locus (NOD), were a kind gift from Vijay Kuchroo (Harvard University, Cambridge, MA) and were previously described . Mice used for phenotypic analyses of salivary gland infiltrating cells were 14‐ to 15‐week‐old females and 19‐ to 21‐week‐old males.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation of submandibular salivary glands and exorbital lacrimal glands was quantified as previously described . Briefly, glands were formalin‐fixed, processed and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation